THEORY ANALYSIS OF LEGAL CHANGE IN SHARIAECONOMIC LEGAL POLICY IN INDONESIA - Eman Suherman (Islamic Studies Journal (ISLAM), 2024)
In the last few decades, sharia economic law has become the focus of attentionin Indonesia. With the world's largest Muslim population, the country has great potential todevelop a financial and economic system based on sharia principles. The theory of legalchange plays an important role in understanding and analyzing the process of implementingeconomic law policies, especially sharia economic law in Indonesia. The methodology used inthis journal will involve analysis of documents, including laws and regulations, courtdecisions, as well as related literature. In addition, case studies on certain sharia economiclaw policies can also be carried out to provide a deeper understanding of the legal changesthat have taken place. Sharia economic law in Indonesia has undergone significant changesover time. Starting from the adoption of laws that support the establishment of Islamic banksto the establishment of supervisory institutions and issuance of more specific regulations, thislegal change illustrates Indonesia's commitment to developing the Islamic economic sector.Changes in sharia economic law in Indonesia have a significant impact on sustainableeconomic development. Through inclusivity and empowerment, stability and economicgrowth, sharia economic law can make an important contribution in achieving sustainableeconomic development goals. This research is expected to provide a valuable contribution tothe development of a theory of legal change as well as a better understanding of theimplementation of sharia economic law policies in Indonesia.